A prospective, randomize study of comparison of lateral internal sphincterotomy versus Lord’s anal dilatation in chronic anal fissure - Kumar, Dhiraj; Negi, Anil; Kumar, Neeraj; Pandey, Avinash (International Surgery Journal, 2018)
Background: Surgical techniques for management of chronic anal fissure are Lords anal dilatation (LAD) and Lateral internal sphincterotomy (LIS). The aim of this study is to compare the symptoms, post-operative complications and recurrence risk of the above two techniques. Methods: It was a prospective, randomized controlled trial done in department of General Surgery of a tertiary care hospital from June 2016-May 2017. A total of 100 patients lined up for surgical management of CAF were divided into two groups (50 each). In group A, 50 patients underwent LAD and in group B, 50 underwent LIS. Patients were followed up for 6 months following surgery for pain, bleeding, incontinence, post-operative hospital stay and recurrence. Wong Baker scale, Modified Longo score and Wexner scales were used for assessment of pain, constipation and incontinence respectively. Various post-operative symptoms, complications and recurrence risk were evaluated post operatively at 24 hours, before discharge from the hospital, 1st, 3rd and 6th months of operation respectively. Results: Male female ratio was 1.7:1. Most common presenting complaint was pain seen in 96% patients. Sentinel tag at 6 o’clock position was seen in the majority (93%) patients on presentation. Except for pain score, which was statistically more significant at 24 hours postoperatively in the LAD group (p=0.012), there was no statistical difference between the two groups when compared at different points of evaluation for symptoms, complications and recurrence (p=0.565). Conclusions: With minor difference in pain, Lord’s dilatation has similar post-operative symptoms; complications and recurrence risk when compared with lateral internal sphincterotomy procedure, for management of CAF and can be safely performed.